Behavioral Economic Demand for Alcohol among Young Adults who Engage in Simultaneous Alcohol and Marijuana Use. Issue 2 (April 2020) - Ramirez, Jason J.; Cadigan, Jennifer M.; Lee, Christine M.
Background: Young adults (YAs) who engage in simultaneous alcohol and marijuana use (SAM) may combine substances due to enhanced subjective effects, and as a result, may place greater value (e.g., spend more resources) on alcohol relative to YAs who consume alcohol but do not engage in SAM. The aim of the current study was to evaluate behavioral economic demand for alcohol among YAs who reported SAM ( n  = 101) relative to alcohol use only ( n  = 316), and concurrent alcohol and marijuana use (CAM; n  = 63). Methods: YAs (18–25 years old) recruited from the community completed an online assessment that included the Alcohol Purchase Task as well as past month alcohol, marijuana, and SAM use. Results: Analyses of covariance demonstrated that YAs who reported SAM had significantly higher O max values (maximum overall expenditures on alcohol) than those who reported CAM, and both YAs who reported SAM and alcohol-only had significantly higher P max values (maximum inelastic price per drink) than YAs who reported CAM. Conclusions: YAs that engage in SAM show an increased willingness to spend resources on alcohol. Elevated demand is not associated with concurrent use of multiple substances, but rather the combined (i.e., overlapping) use of substances.